MODELING A MATHEMATICAL MODEL OF CIRCULATING WATER COOLING PROCESSES IN THE MATLAB SIMULINK PACKAGE - Abdullajonov Sirojiddin Sadirdin o‘g‘li; Polvonov Omonjon Xusanboy o’g’li; Najmitdinov Zikrillo Zuxriddin o’g’li (Web of Journals Publishing, 2024)
To learn how to cool water by supplying air to the operating area of the cooling tower, a mathematical model of the processes of cooling circulating water in the thermal supply system of the thermal power plant was modeled in the matlab simulink package.
Keywords: energy, temperature, circulation, condenser, steam turbine, steam condensation, fuel, technical water.